MENINGKATKAN KEMAMPUAN SAINS MENGENAL BENDA CAIR MELALUI METODE EKSPERIMEN - Khairani Amalia; sri saparahayuningsih; Anni Suprapti (Jurnal Ilmiah POTENSIA, 2018)
Problems in this research is whether through experiment method can improve the ability of science to know liquid object at group B5 TK Witri I of Bengkulu City? The purpose of this class action research is to increase the ability of science to know the liquid through the experimental method at group B5 TK Witri I of Bengkulu City. This research is a classroom action research (CAR). The result of this research is through experiment method can improve the ability of science to know liquid objects. Evident from the average score of children's science skills in the first cycle reached an average grade of 3.53 with 70.6% classical completeness is on the enough criteria then in cycle II the average value of children reached 4.16 with classical completeness 83.2% is in good criteria. It is suggested for the next researcher to use experimental method in improving children's science skill especially predicting aspect. Key Words : The Science Abilities, Experiment Method, Soluble And Insoluble Objects.